(untitled) (Global Journal of Management and Business Research, 2021)
The objective of this research is to highlight the factors driving the structural and behavioural contingencies to the adoption of dashboards by small and medium sized enterprises (SMEs) in the Cameroonian context. Using data collected from 314 SMEs, we conducted an exploratory analysis, in order to investigate the factors that could have an influence on the use of dashboards and a multiple correspondence factorial analysis in order to identify the characteristics of SMEs using dashboards. On the other hand, a binary logistic regression was done to unveil the factors that stand behind the usage of dashboards in Cameroonian SMEs. Our findings indicate that the formal nature of the SME, the power delegation, the presence of an experienced leader, the pressure of foreign competition, the age of the company, the use of follow-up software in organizational processes and the implementation of a system to reward the employees when they achieve positive results, are the factors that enable the adoption of the dashboard.